2022
DOI: 10.1038/s41390-022-02297-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulation and golden hour practices in extremely preterm infants: an international survey

Abstract: Background Are thermoregulation and golden hour practices in extremely preterm (EP) infants comparable across the world? This study aims to describe these practices for EP infants based on the neonatal intensive care unit’s (NICUs) geographic region, country’s income status and the lowest gestational age (GA) of infants resuscitated. Methods The Director of each NICU was requested to complete the e-questionnaire between February 2019 and August 2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 23 publications
0
10
0
8
Order By: Relevance
“…Following the international recommendations, the protocol elaborated in this study was organized under four main pillars: cardiopulmonary stabilization, and prevention of hypothermia, hypoglycemia and infection. Actions such as setting the ambient temperature, using a heated field, equipment for fractional oxygen supply and agility in obtaining venous access are important to meet these pillars, as observed in other studies ( 3 - 4 , 9 - 10 ) .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Following the international recommendations, the protocol elaborated in this study was organized under four main pillars: cardiopulmonary stabilization, and prevention of hypothermia, hypoglycemia and infection. Actions such as setting the ambient temperature, using a heated field, equipment for fractional oxygen supply and agility in obtaining venous access are important to meet these pillars, as observed in other studies ( 3 - 4 , 9 - 10 ) .…”
Section: Discussionmentioning
confidence: 89%
“…National and international research studies indicate that postpartum hypothermia poses a risk to the vitality of PTNBs and that it is a predictive factor of morbidity and mortality, regardless of gestational age. Heat loss cannot be overcome by heat production, mainly in premature infants, and the team must carry out interventions for thermal control while caring for the PTNB ( 4 , 6 , 22 - 23 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the complexity of care that needs to be delivered within the Golden Hour, many neonatal units rely on evidence-based bundles of care, based on specific needs of the unit, for example, improving admission temperatures, or reducing rates of bronchopulmonary dysplasia or intraventricular hemorrhage 12–14…”
Section: Available Knowledgementioning
confidence: 99%
“…10,11 Because of the complexity of care that needs to be delivered within the Golden Hour, many neonatal units rely on evidence-based bundles of care, based on specific needs of the unit, for example, improving admission temperatures, or reducing rates of bronchopulmonary dysplasia or intraventricular hemorrhage. [12][13][14] Although having the right equipment available is critical to completing a quick and effective admission, emerging research suggests that teamwork may be more important than previously suggested. 5,6,15 It is critical that all members of admission teams understand their role and operate on a shared mental model.…”
Section: Available Knowledgementioning
confidence: 99%